2020
DOI: 10.1371/journal.pmed.1003272
|View full text |Cite
|
Sign up to set email alerts
|

State-level prescription drug monitoring program mandates and adolescent injection drug use in the United States, 1995–2017: A difference-in-differences analysis

Abstract: Background Prescription opioid misuse is an ongoing crisis and a risk factor for injection drug use (IDU). Few studies have evaluated strategies for preventing opioid or IDU initiation among adolescents. We evaluated changes in the proportion of adolescents reporting IDU before and after prescription drug monitoring program (PDMP) mandates were implemented in 18 states compared to 29 states without such mandates. Methods and findings This difference-indifferences analysis used biannual Youth Risk Behavioral Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Overall, half of the studies involved patients [9,18,22–24,26,27,32,34,36–38,41–43,45,46,48,50,53,54,59,62,63,65,66,71,73,75,77–80,84–86,88,90,93,95,97,98,100,101,104,105,108–110,115–118,121,123,125,130,131,134,140,144,146,147,149,151,152,154–156,158,159,161,163,165,167] and 47% included health‐care providers [11,19,20,25,29,30,33,35,37,39,40,43,44,49,51,54–61,67–69,71,72,74,76,80–83,87,91,93,94,96,102,103,106,111–114,119,120,122,124,125,127,128,130,132,133,136–139,141,143,145,147,148,150,153,157,160,162,165]. Some studies included both patient and provider populations [36, 37, 54, 59, 80, 93, 130, 147, 166].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, half of the studies involved patients [9,18,22–24,26,27,32,34,36–38,41–43,45,46,48,50,53,54,59,62,63,65,66,71,73,75,77–80,84–86,88,90,93,95,97,98,100,101,104,105,108–110,115–118,121,123,125,130,131,134,140,144,146,147,149,151,152,154–156,158,159,161,163,165,167] and 47% included health‐care providers [11,19,20,25,29,30,33,35,37,39,40,43,44,49,51,54–61,67–69,71,72,74,76,80–83,87,91,93,94,96,102,103,106,111–114,119,120,122,124,125,127,128,130,132,133,136–139,141,143,145,147,148,150,153,157,160,162,165]. Some studies included both patient and provider populations [36, 37, 54, 59, 80, 93, 130, 147, 166].…”
Section: Resultsmentioning
confidence: 99%
“…The extracted data from the included studies were then classified into main conceptual categories and summarised to align with the scoping review objective and research questions. The data extraction results are presented in Tables S1 and S2 [18–166], Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only three studies have examined the impact of PDMPs on opioid-related outcomes among adolescents, and none have focused on prescription pain medication misuse among adolescents. Earlywine, Hadland & Raifman reported that PDMPs with mandated prescriber use significantly reduced injection drug use among 17-18 year olds [10]; Toce et al found significant long-term decreases in opioid poisoning rates among those aged 0-4 years, 5-9 years, and 15-19 years following PDMP implementation [11]; and Theodorou et al reported no statistically significant change in the rate of postoperative opioid prescriptions for California patients aged less than 18 years after a change to the state's PDMP in 2018 [12].…”
Section: Introductionmentioning
confidence: 99%
“…6 There has been limited research evaluating the use and impact of PDMP on the pediatric population, and knowledge and use of the PDMP by pediatric providers has been limited. [7][8][9] The objective of this study was to evaluate the use of an integrated PDMP into an EHR within a children's hospital, and subsequent opioid prescribing patterns.…”
Section: Introductionmentioning
confidence: 99%